Insect diversity and new records from mangrove forests of Cat Ba National Park, Vietnam, using multi-method sampling - THI ANH NGUYET NGUYEN; PHU VAN PHAM; TRANG QUYNH LE; THANH SON NGUYEN; ANH DUC TRAN; CUONG VAN DUONG (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Nguyen TAN, Pham VP, Le TQ, Nguyen TS, Tran AD, Duong VC. 2025. Insect diversity and new records from mangrove forests of Cat Ba National Park, Vietnam, using multi-method sampling. Biodiversitas 26: 4606-4617. Insects play key ecological roles in mangrove ecosystems, contributing to pollination, decomposition, and trophic interactions. These functions are critical for maintaining the structure, productivity, and resilience of mangrove habitats. Despite their ecological importance, insect communities in mangroves remain poorly studied in many parts of Southeast Asia, including Vietnam. Cat Ba National Park, located on an archipelago in northern Vietnam, encompasses diverse ecosystems such as tropical evergreen forests, mangrove forests, tidal flats, marine lakes, coral reefs, and soft-bottom habitats. Among these, mangrove forests are a vital natural resource for tropical coastal regions, including those of Cat Ba. This study presents the first comprehensive survey of insect diversity in the mangrove forests of Cat Ba National Park. Using multiple sampling methods, including sweep nets, light traps, and yellow pan traps, we recorded 163 insect species, representing 135 genera, 57 families, and 11 orders. Hemiptera was the most species-rich order (37 species), followed by Lepidoptera (31 species) and Diptera (28 species). Notably, eight species and four genera are newly recorded for Vietnam, highlighting the potential of mangrove habitats as reservoirs of undocumented biodiversity. Sweep nets proved most effective (which obtained 110 species), particularly for Hemiptera and Hymenoptera, followed by light traps (62 species), which primarily captured Lepidoptera (moths). Yellow pan traps yielded only 10 species, mainly Diptera. This study establishes a crucial baseline for future monitoring and offers insights applicable to other mangrove ecosystems in Southeast Asia that remain understudied.